The Learning Curve of Unilateral Biportal Endoscopic (UBE) Spinal Surgery by CUSUM Analysis - Chen, Lei; Zhu, Bin; Zhong, Hua-zhang; Wang, Yi-guo; Sun, Yi-song; Wang, Qi-fei; Liu, Jian-jun; Tian, Da-sheng; Jing, Jue-hua (Frontiers in surgery, 2022)
To assess the learning curve of the unilateral biportal endoscopic (UBE) technique for the treatment of single-level lumbar disc herniation by cumulative summation (CUSUM) method analysis. A retrospective analysis was conducted to assess 97 patients' general condition, operation time, complications, and curative effect of single segmental UBE surgery performed by a spinal surgeon in his early stage of this technique. The learning curve of operation time was studied using a CUSUM method, and the cut-off point of the learning curve was obtained. The operation time was 30 - 241(97.9 ± 34.7) min. The visual analog scale score of lower limb pain decreased from 5.75 ± 0.81 before the operation to 0.39 ± 0.28 at the last follow-up ( < 0.05). The Oswestry disability index score decreased from 66.48 ± 4.43 before the operation to 14.57 ± 3.99 at the last follow-up ( < 0.05). The CUSUM assessment of operation time revealed the learning curve was the highest in 24 cases. In the learning stage (1-24 cases), the operation time was 120.3 ± 43.8 min. In the skilled stage (25-97 cases), the operation time was 90.5 ± 27.8 min. About 24 cases of single segmental UBE operation are needed to master the UBE technique.